2019
DOI: 10.3390/app9214527
|View full text |Cite
|
Sign up to set email alerts
|

AR Graphic Representation of Musical Notes for Self-Learning on Guitar

Abstract: Despite being one of the most commonly self-taught instruments, and despite the ready availability of significant amounts of didactic material, the guitar is a challenging instrument to learn. This paper proposes an application based on augmented reality (AR) that is designed to teach beginner students basic musical chords on the guitar, and provides details of the experimental study performed to determine whether the AR methodology produced faster results than traditional one-on-one training with a music teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 36 publications
1
26
0
3
Order By: Relevance
“…Besides, users comment on the drawback that the use of marks is a disadvantage since it must always be in front of the camera. Del Rio et al [21] conducted a SUS like the one presented in this article and obtained a similar evaluation of the usability of the system. In cases where there is mention of user perception, participants indicated that it is easy to use and that they were interested in learning.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Besides, users comment on the drawback that the use of marks is a disadvantage since it must always be in front of the camera. Del Rio et al [21] conducted a SUS like the one presented in this article and obtained a similar evaluation of the usability of the system. In cases where there is mention of user perception, participants indicated that it is easy to use and that they were interested in learning.…”
Section: Discussionmentioning
confidence: 77%
“…A good example of this is the AR system proposed by Löchtefeld et al [20], who designed and implemented an AR model that uses mobile projector mounted on the guitar's headstock to project instructions that facilitate correct finger placement. Another recent proposal for learning the guitar suggests using coloured finger markers and then projecting the corresponding colours onto the strings and frets using AR to instruct learners how to perform a chord [21]. The aforementioned studies do not display hand movements involved in the chord transitions of short melodies.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential that teachers look for new teaching techniques based on ICTs to understand their students [102]. Through this research, we found a priceless tool in the computer game, as its use was highly motivating for the students, arousing great interest and expectation.…”
Section: Discussionmentioning
confidence: 91%
“…Based on the results, we believe that students need experiences that allow them to work collaboratively, and that these have an impact on them. Students need to see meaning in what they do, feel at ease, and assess and comment on their own successes or failures [27,[33][34][35]. In this sense, the self-reporting provided valuable information by making it clear that you can work interdisciplinarily in the math class.…”
Section: Discussionmentioning
confidence: 99%